Validation of a disease-specific health-related quality of life measure in adult Italian patients with systemic lupus erythematosus: LupusQoL-IT. (July 2014) - Conti, F; Perricone, C; Reboldi, G; Gawlicki, M; Bartosiewicz, I; Pacucci, VA; Massaro, L; Miranda, F; Truglia, S; Alessandri, C; Spinelli, FR; Teh, L-S; et al.
Objective: The objective of this paper is to assess the validity of a linguistically validated version of the Lupus Quality of Life (LupusQoL © ) in Italian patients affected by systemic lupus erythematosus (SLE). Methods: Consecutive SLE patients completed the Italian version of the LupusQoL © and the Short Form (SF)-36. Disease activity was evaluated by the SLE disease activity Index-2000 (SLEDAI-2 K), and chronic damage by the Systemic Lupus International Collaborating Clinics/American College Rheumatology (ACR) Damage Index score (SDI). Internal consistency and test-retest reliability, convergent and discriminant validity were examined. Factor analysis with varimax rotation was performed. Results: A total of 117 Italian SLE patients (M:F 13:104; mean age 40.6 ± 11.6 years, mean disease duration 127.5 ± 94.1 months) were recruited into the study. The Italian version of the LupusQoL © demonstrated substantial evidence of convergent validity in these patients when compared with equivalent items of the SF-36. In addition, the LupusQoL © discriminated between patients with different degrees of disease activity as measured by the SLEDAI-2 K. SLE patients with higher disease activity (SLEDAI-2K ≥4) showed poor QoL compared with those with lower disease activity (SLEDAI-2K <4), with significant differences in the domains of physical health, planning, burden to others and fatigue ( p  = 0.001, p  = 0.04, p  = 0.03, p  = 0.04, respectively). The confirmatory factor analysis using the eight domain loadings of the 34 items showed a poor fit (χ 2 /degree of freedom (df) 2.26, χ 2  = 1128.6 ( p  < 0.001), root mean square error of approximation (RMSEA) = 0.167; goodness-of-fit index (GFI) = 0.606, comparative fit index (CFI) = 0.649)). Screeplot analysis suggested a five-factor loading structure and confirmatory factor analysis result of which is similar to the eight-factor model. A good internal consistency was observed (Cronbach's α 0.89–0.91). Test-retest reliability was good to excellent between baseline and day 15 (intraclass correlation coefficient (ICC) 0.90–0.98). Conclusion: The Italian version of the LupusQoL © is a valid tool for adult patients with SLE.